Learning Strategy of Think Talk Write Based Inquiry Approach Toward the Scientific Communication Ability of Students - Auliasari, Vety; Supriyadi, Supriyadi; Linuwih, Suharto (Universitas Negeri Semarang, 2019)
This study has purpose to determine the comparison of the scientific communication ability of students between groups using the think talk write learning based inquiry approach to groups using the experimental learning, and determine the relationship between students' initial ability and students' scientific communication ability. The study was conducted with an experimental approach carried out in grade XI Persiapan Grafika SMK Islam Al Bisyri Semarang, by comparing the Think Talk Write learning groups based inquiry approach to the experimental learning. The variables studied were scientific communication ability obtained through observation during the learning process. The data were analyzed using Mann Whitney U and Spearman Rank. The results showed that the scientific communication ability of the think talk write based inquiry approach learning group based on the inquiry approach reviewd from four components, the Think Talk Write based inquiry approach learning group had the ability to access and utilize the latest library resources, the ability to contribute ideas in group work, the ability to prepare reports in accordance with the guidelines for scientific paper reports, it is better than the experimental learning, however, in the component of communicating products or reports verbally (presentations) did not show a significant difference between the think talk write based inquiry approach learning group and the experimental learning group. The initial ability of students does not affect the scientific communication ability of students in the think talk write learning group based inquiry approach and experimental learning groups.